Deconstructing Incidents of Campus Sexual Assault: Comparing Male and Female Victimizations. (April 2019) - Budd, Kristen M.; Rocque, Michael; Bierie, David M.
Research on campus sexual assault (CSA) has almost exclusively drawn on self-report data, examined undergraduates (i.e., students aged 18-24), and focused on female victimization. The few studies which included male CSA victims generally had fewer than 100 male subjects, which makes important statistical analyses difficult. To build upon prior literature and expand knowledge on male CSA victimization, we analyzed more than 5, 000 incidents of CSA that were reported to police from across the United States using National Incident-Based Reporting System data (NIBRS; 1993-2014). We expanded victim age ranges to include those 17 to 32 years old and investigated more male CSA victimizations than prior work to date, approximately 350 incidents. Comparisons of male victim versus female victim CSA incidents, estimated via multivariate logistic regression, revealed several important patterns. Although both male and female victims were approximately 19 years old on average, perpetrators who assaulted females tended to be 23 years old while those assaulting males were on average 29. While 1% of CSA perpetrators offending against female victims were themselves female, 17% of perpetrators offending against male victims were female. Finally, CSA incidents with male victims were more likely to include multiple offenders, but less likely to involve stranger or Black perpetrators and also less likely to result in injuries relative to CSA incidents with female victims. Implications are discussed in terms of policing practices, and we pose new questions to the field regarding the study and prevention of CSA.